2019
DOI: 10.29136/mediterranean.488149
|View full text |Cite
|
Sign up to set email alerts
|

Yerli mandarin x Carrizo sitranjı melezlerinde, embriyo kurtarma tekniğinde embriyo gelişim aşaması ve GA3 dozlarının optimizasyonu

Abstract: Many difficulties are exist in citrus breeding due to incompatibility, long juvenility, sterility and nucellar embryo. Zygotic embryo in the seeds of polyembryonic citrus cultivar is degenerated by nucellar embryos during embryo development. Accordingly, in vitro embryo culture is a useful tool in citrus breeding, since it assures embryo germination and development. In this study, Common mandarin x Carrizo citrange were crossed in order to produce new rootstock genotypes. Immature embryos were taken from fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Several studies have shown that Murashige and Skoog (MS) media modified by Morel & Wetmore vitamins (VMW) are suitable for in vitro growth of citrus, as reported in somatic embryogenesis of mandarin (Purwito et al 2015), somatic embryogenesis from endosperm tissue of C. nobilis (Kosmiatin et al 2014), and in micropropagation and micrografting of Japansche Citroen (Putra et al 2015). Conversely, Murashige & Tucker (MT) medium is also widely utilized in citrus plants, including in vitro propagation of Thomson navel sweet oranges (Esmaeilnia & Dehestani 2015) and embryo rescue in progenies resulting from crosses between mandarin and Carrizo citrange (Kurt & Ulger 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that Murashige and Skoog (MS) media modified by Morel & Wetmore vitamins (VMW) are suitable for in vitro growth of citrus, as reported in somatic embryogenesis of mandarin (Purwito et al 2015), somatic embryogenesis from endosperm tissue of C. nobilis (Kosmiatin et al 2014), and in micropropagation and micrografting of Japansche Citroen (Putra et al 2015). Conversely, Murashige & Tucker (MT) medium is also widely utilized in citrus plants, including in vitro propagation of Thomson navel sweet oranges (Esmaeilnia & Dehestani 2015) and embryo rescue in progenies resulting from crosses between mandarin and Carrizo citrange (Kurt & Ulger 2019).…”
Section: Introductionmentioning
confidence: 99%